The Relationship Among Wellness Tourism, Attitude Toward Wellness Activities, Social Media Norms, Satisfaction Wellness Activities and Intention to Participate Wellness Activities. Case Study: Thailand Riviera Area - Phetsome, Suppacha; Ashton, Suwaree (Rajapark Journal, 2024)
This study focuses on wellness tourism in the Thailand Riviera Area (Petchaburi, Prachub Kiri Khun, Chumporn, and Ranong). The objective of this study is to examine the cause effects of Thailand tourists’ intent to participate in wellness activities, attitude toward wellness activities, social media norms, and satisfaction with wellness activities. Questionnaires were collected from 308 Thai tourists who traveled to the Thailand Riviera area and collected data that was then analyzed using structural equation modeling (SEM). The structural model proved to be a well-fitting model. The results indicate that the tourists’ attitude toward wellness activities and social media norms has an indirect effect on satisfaction with wellness activities. At the same time, satisfaction with wellness activities has an indirect effect on the intention to participate in wellness activities.